1990
DOI: 10.1002/(sici)1097-4571(199006)41:4<254::aid-asi4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic derivation of name access points in cataloging

Abstract: This artlcle reports the results of research designed to explore the feasibility of automatically deriving name access points from machine-readable title pages of English language monographs. Two questions were asked: (1) To what degree is it possible to specify formal criteria for extracting from the title pages of monographs in machine-readable form the names of those persons and corporate bodies who have contributed significantly to the creation of the monographs in question? and (2) Are title page data ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Difl'erent chapters ofthe cataloging rules have been studied from a variety of perspectives, with the common pu{pose of enhancing their understanding and suggesting how the nrles could be improved in {'urther editions. Svenonius and Molto (1990), Davies (1992), and Weibel (1992) prepared extensive reviews of automated descriptive cataloging and related research. They point to Sandberg-Fox (1972) as the ffrst io work on thii topic.…”
Section: Crrerocrnc Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Difl'erent chapters ofthe cataloging rules have been studied from a variety of perspectives, with the common pu{pose of enhancing their understanding and suggesting how the nrles could be improved in {'urther editions. Svenonius and Molto (1990), Davies (1992), and Weibel (1992) prepared extensive reviews of automated descriptive cataloging and related research. They point to Sandberg-Fox (1972) as the ffrst io work on thii topic.…”
Section: Crrerocrnc Rulesmentioning
confidence: 99%
“…However, the researchers f'urther found that manv of the personal and corporate names tiat appeared on title pages, preliminaries and tables of contents were neither authors nor people or bodies whose function was related to authorship. Svenonius and Molto (1990) investiname access points. The success rate was measured by the number of correctlv identified access points (all names), anl in terms of precision (the number of cornarnes, 95Vo werc also chosen as access points in LC and NLM cataloging records.…”
Section: Choice and Form Of Access Pointsmentioning
confidence: 99%
“…There have been attempts to design procedures for the automated selection of access points, 19,20 and to develop expert systems for fully automated cataloguing. 21,22 However, the recent appearance of online public access catalogs (OPACs) and the cataloguing of Internet sources have reoriented current research.…”
Section: Introductionmentioning
confidence: 99%